ANALYSIS OF TAX IMPOSITION ON THE DISTRIBUTION OF THE ENDOWMENT FUND SERVICE PROGRAM IN THE FIELD OF EDUCATION: (CASE STUDY AT THE INDONESIAN EDUCATION FUND MANAGEMENT AGENCY) - Saud, Yehezkiel Victor; Khusnaini; Putra, Fahdiansyah (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2025)
Vision Indonesia Gold 2045 depicts Indonesia as an advanced country based on knowledge and innovation, rooted in the culture of the Archipelago. Higher education institutions play a vital role in creating and disseminating knowledge through research, as well as building superior human resources. The Educational Fund Management Institution (LPDP), as a Public Service Agency (BLU), manages the Endowment Fund in the field of education. In its disbursement to beneficiaries, tax imposition occurs in the form of VAT collection and income tax deductions. This has led to differing views between LPDP and the Directorate General of Taxes (DJP): DJP considers the tax imposition appropriate, while LPDP asserts that it should not be imposed. This research aims to understand the application of taxation on those funds and analyze their treatment. The method used is a qualitative approach through literature studies and interviews, with data analysis using NVivo software to develop coding and mind maps. The research results show that VAT is imposed on research services and income tax on the additional economic capacity of beneficiaries. A grey area has also been found in the applicable tax provisions. It is recommended that LPDP propose specific regulations regarding the taxation of the Endowment Fund in the field of education to the Fiscal Policy Agency (BKF) and DJP.